Of microbes and mothers: evaluating the complex maternal-neonatal interaction and microbiome-immunity development with novel Lactobacillus vaccination - Ecton, Kayl E., author; Abdo, Zaid, advisor; Dean, Gregg, advisor; Wrighton, Kelly, committee member; Vilander, Allison, committee member; Argueso, Lucas, committee member (Colorado State University. Libraries, 2024)
The task of identifying an optimal vaccination strategy for neonates has been challenging scientists and physicians alike. Multiple factors contribute to the difficulty in establishing an optimal platform including the complexity of the maternal-fetal dyad, a neonatal Th2 skewed profile and the role of the parallel development of the immune system and the gut microbiome (8). Disease remains a main cause of infant morbidity and mortality, encouraging the discovery of novel infant vaccinations to be delivered during the first 28 days of life to provide protection (41). Passive protection from the maternal transfer of transplacental IgG and both IgG and IgA in breastmilk has a limited window of operation, leaving the maturing neonate at risk (128). Although exact mechanisms remain to be elucidated, here we examine the complex crosstalk between mother-fetus and maternal-neonate dyads, neonatal microbiome-immunity development, and optimal delivery strategies for neonatal vaccine development. In this dissertation we investigated the role of maternal infection prior to gestation, neonatal challenge after vaccination, and vaccine effectiveness after exposure to virus. We evaluated the use of a novel vaccine platform developed previously in the lab as an orally delivered mucosal targeting subunit vaccine in Lactobacillus acidophilus. We investigated the effectiveness of the recombinant vaccine with and without adjuvants in a neonatal experimental design model and discovered increased virus specific responses in neonates vaccinated with adjuvants when challenged with rotavirus. We show a significant impact of maternal influence on neonatal outcomes. Beyond the immunogenic strength of the novel Lactobacillus acidophilus vaccine platform in neonates, we identified induced shifts to the gut microbial communities that occurred with vaccination or infection. We saw a shift in the gut microbiome over the course of a 7-day rotavirus challenge in neonates that did not return to baseline during the observation period, even after no virus shedding was detected in fecal samples. We also evaluated the impact of different doses, 1x106 CFU/dose and 1x109 CFU/dose, on the immune response and the gut microbiome. We confirmed the role of fecal microbiome transplants in breeding does to normalize for the maternal microbiome prior to gestation. Our results indicate that there are modifications to the gut microbiome and changes in immune antibodies during vaccination and infection. While we did not pursue a specific mechanism crosslinking the maternal-neonatal interaction and the gut-immunity relationship, we do consider the presence of such a connection.